A LITERATURE REVIEW ON COMMUNICATION STRATEGIES IN LANGUAGE LEARNING - Oweis, Thelal (European Scientific Journal, ESJ, 2013)
Communicating successfully means to pass on meaningful messages to the listeners. In order to achieve a successful level of communication in situations, where learners face problems when there is a mismatch between their communication goals and their linguistic resources, they tend to use devices to improve their level of communication; these devices are called Communication Strategies.This paper reviews and discusses the theoretical background of the study of Communication strategies in language learning. The first part of the paper presents the most common definitions of the Communication Strategies. The second part attempts to explain the relationship between Communicative Competence and Communication Strategies. The third part describes the types, taxonomies and the origins of the Communication Strategies. The final part sheds the light on a number of empirical studies related to types of Communication Strategies and the relationship between linguistic proficiency and Communication Strategies choice in the learner’s first language and his/her second language.